2021
DOI: 10.1177/2515841420984572
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the treatment of juvenile idiopathic arthritis–associated uveitis

Abstract: Juvenile idiopathic arthritis–associated uveitis has an estimated prevalence of 10–20% in patients with juvenile idiopathic arthritis, making it the most common cause of chronic anterior uveitis in children. Prompt treatment is important to prevent development of ocular complications and permanent vision loss. In this review, we will discuss the use of immunosuppression in treatment of juvenile idiopathic arthritis–associated uveitis. This will include the use of conventional immunosuppressants, such as methot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…Regarding pharmaceutical interventions, first-line treatment strategies for JIA-associated uveitis include topical glucocorticoids, and in the case of synechiae, mydriatic eye drops to prevent an increase in intraocular pressure and cataract development. If topical treatment fails to induce stable remission, systemic treatments are added, which may include corticosteroids, disease-modifying antirheumatic drugs (DMARDs), and biopharmaceutical agents [102][103][104][105]. Regarding the use of corticosteroids, paucity of evidence underpins the most effective route of administration (oral vs. intravenous), dosing, and treatment duration.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding pharmaceutical interventions, first-line treatment strategies for JIA-associated uveitis include topical glucocorticoids, and in the case of synechiae, mydriatic eye drops to prevent an increase in intraocular pressure and cataract development. If topical treatment fails to induce stable remission, systemic treatments are added, which may include corticosteroids, disease-modifying antirheumatic drugs (DMARDs), and biopharmaceutical agents [102][103][104][105]. Regarding the use of corticosteroids, paucity of evidence underpins the most effective route of administration (oral vs. intravenous), dosing, and treatment duration.…”
Section: Treatmentmentioning
confidence: 99%
“…In patients with failing or with insufficient response to DMARDs, biopharmaceutical drugs will be used, usually targeting TNF and IL-6 pathways [104]. The SYCAMORE trial [111] demonstrated the significant benefit of anti-TNF treatment (adalimumab) in patients failing on methotrexate, and the ADJUVITE trial [112] was in favor of using adalimumab in patients with early-onset, chronic anterior uveitis, which is in most cases associated with JIA, in case of inadequate response to topical therapy and methotrexate.…”
Section: Treatmentmentioning
confidence: 99%
“…Continued translational research and clinical trials will help us learn more about the biology that underpins disease, with the goal of developing safer, more effective medicines and possibly a cure [6]. Azathioprine, Cyclosporine, Mycophenolatemofetil, Chlorambucil [35]. Some of the treatment strategies that being used start normally with NSAIDs for 4 to 6 weeks, then move on to DMARDs, most often methotrexate, if the NSAIDs don't work.…”
Section: Management and Treatmentmentioning
confidence: 99%
“…Monoclonal antibodies, soluble receptors, cytokines, and cytokine antagonists are among the 'biologics,' which are huge, complex molecules produced from living organisms or synthesised using recombinant DNA technology [35].…”
Section: Biological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation